Why Phenomenal Zombies Are Conceivable Whereas Anti-Zombies Are not (Actual Problems of Mind, 2019)
In this article, I discuss Keith Frankish’s attempt to neutralize the zombie argument against materialism with a closely parallel argument for physicalism, the anti-zombie argument, and develop David Chalmers’ reply to this species of arguments. I support Chalmers’ claim that the conceivability of situations like the existence of an anti-zombie is problematic with an analysis that makes it plausible that the idea of an anti-zombie is incoherent, and argue that to counter this, a materialist should deny the absence of a priori entailment from the physical to the phenomenal; however, this would involve the denial of the conceivability of zombies and so make the anti-zombie argument superfluous.
Keywords: anti-zombie; coherence; conceivability; phenomenal zombie; physicalism